1987
DOI: 10.1159/000281948
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Tumors: Presentation and Role of Diagnostic Delay

Abstract: 180 patients with testicular germ cell tumors were evaluated in a retrospective study concerning the features of presentation and diagnostic delay. Mean duration of symptoms was 170 days, being different for semi-noma and nonseminoma, and showing a continuous decrease since 1969. Duration of symptoms was longest in stage I seminoma. In the nonseminoma group the longest interval was observed in stage III. It is concluded that only in nonseminoma a prolonged delay exerts adverse effects on prognosis. Short delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 16 publications
(21 reference statements)
0
24
0
Order By: Relevance
“…Late stage diagnosis of TGCT, particularly nonseminomatous TC, has been shown to be a risk factor for increased TGCT-specific mortality [40,60]. We were able to find 2 studies that specifically address the association of stage at diagnosis of TC and SEP. Dieckmann et al found that lower educational levels were related to delays in diagnosis for nonseminomatous TGCT in 180 German men [60].…”
Section: Sep and Stage At Diagnosismentioning
confidence: 97%
See 3 more Smart Citations
“…Late stage diagnosis of TGCT, particularly nonseminomatous TC, has been shown to be a risk factor for increased TGCT-specific mortality [40,60]. We were able to find 2 studies that specifically address the association of stage at diagnosis of TC and SEP. Dieckmann et al found that lower educational levels were related to delays in diagnosis for nonseminomatous TGCT in 180 German men [60].…”
Section: Sep and Stage At Diagnosismentioning
confidence: 97%
“…Late stage diagnosis of TGCT, particularly nonseminomatous TC, has been shown to be a risk factor for increased TGCT-specific mortality [40,60]. We were able to find 2 studies that specifically address the association of stage at diagnosis of TC and SEP. Dieckmann et al found that lower educational levels were related to delays in diagnosis for nonseminomatous TGCT in 180 German men [60]. In contrast, Toklu and colleagues reported on 140 Turkish men seen in their clinic from 1994-1995 and found that stage of diagnosis did not statistically differ by income level or between college graduates versus non-college graduates [40].…”
Section: Sep and Stage At Diagnosismentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies have shown that delay in presentation is common and may result in metastases and increased mortality and morbidity, especially for patients with nonseminoma. [9][10][11][12] As stage is one of the most significant determinants of survival, the earlier we can detect TC, the greater chance we could achieve longer survival. Early detection of TC theoretically can be improved by spreading medical information on the importance of selfexamination and the curability of TC, and on multimodal treatment possibilities.…”
Section: Quotable Abstractsmentioning
confidence: 99%